Symmetry of dental arches in patients with unilateral primary and secondary cleft palate - Herud, Anna; Borzęcka, Agnieszka; Skiba, Adam (Journal of Stomatology, 2017)
Introduction. Primary and secondary cleft palate may cause disturbances in the development of the maxilla in three spacial dimensions. Patients with this defect are usually characterised by cross-bites, pseudo Class III, and numerous dental disorders. Due to anatomical and functional connection of the maxillary and mandibular structures, anomalies within the maxillary dental arch caused by the cleft may affect inadequate formation of the mandibular dental arch leading to its asymmetry. Aim of the study. To analyse the symmetry of maxillary and mandibular dental arches in patients with unilateral primary and secondary cleft palate using the GOSLON index with scores 4 or 5. Material and methods. Plaster models of dental arches obtained from 21 patients with unilateral primary and secondary cleft palate, who scored 4 or 5 on the GOSLON index were used in the study. The patients’ mean age was 10.6 years. The symmetry of dental arches was assessed in relation to the sagittal and orbital plane, measuring the anterior and posterior width and length of the arches on the cleft and non-cleft side. Results. Clinically observed asymmetry of the maxillary and mandibular dental arch length and width on the cleft and non-cleft side was not confirmed by the statistical analysis. The results of measurements of both dental arches symmetry made on the first molars on the cleft side indicated a statistically significant correlation. Lower values of the width of the maxillary dental arch corresponded to higher values of the mandibular arch width. Whereas the results of measurements of the length of the dental arches revealed that together with an increased length of the maxillary dental arch on the cleft side, an increase in the length of the opposing segment of the mandibular dental arch was observed.